Influência das safras de cana de açúcar na configuração das ilhas de calor urbano em áreas periurbanas em Piracicaba, SP - Coury, Bruno Sigolo (2021)
This work comes from the premise that periurban spaces, in general neglected by the traditional climatological urban studies, also possesses altered environments, with observable negative consequences to their microclimates, like the formation of the Urban Heat Islands (UHIs), since they also present anthropic factors which contribute to this scenario. Besides, it is notable the influence that the surrounding rural environment possesses to these areas, complying to observe in which manner the agricultural activities nearby will influence the climate regions. Being so, this research proposes a visualization of the influence that the spatial variations have to periurban neighborhoods of the municipality of Piracicaba/SP, an interior medium size city, situation that doesn’t make the traditional center of the climatological research, but has presented an accelerated urbanization process, typical of the Brazilian scenario. To this, two periods of obtaining climatological data were defined: before and after the sugarcane harvest, moments in which the rural soil presents bigger territorial differentiation. In the period after the harvest, it was installed measurement sensors in a sugarcane field and in two borderline periurban neighborhoods, which owns different territorial configurations, besides another sensor in a centralized neighborhood, with bigger urbanization, as a reference. So, it was pretended to observe not only the influence of the rural environment to the periurban spaces, but also how the spatial variations inside a same urban space can contribute to different microclimates, as proposes the Local Climate Zones (LCZs) methodology by Stewart & Oke (2012). As an additional practice, mobile transects were simultaneously realized in the rural area an in one of the periurban neighborhoods, allowing bigger comparation between these. The results obtained with the first stage of the collect made possible to visualize a significant bigger difference, between the temperatures of the central neighborhood and the rural area, especially in the final of the dawn, process which is reversed in the beginning of the morning, due to the warmth of the exposed rural soil. The periurban neighborhoods presented in general bigger temperatures than the rural area, although smaller than the central neighborhood, corroborating the contribution that the urban density possesses to the surrounding temperatures. However, the thermal configuration of them varied according to their own spatial arrangement, demonstrating that not only the agricultural environment is relevant, but also the configuration of each periurban area to their respective microclimate.